The Heterogeneous Effects of a Food Price Crisis on Child School Enrollment and Labor : Evidence from Pakistan - Hou, Xiaohui (World Bank, Washington, DC, 2013)
Using a panel survey, this paper investigates how the increase in food prices in Pakistan in 2008-2010 affected children's school enrollment and labor. The causal identification relies on geographical variations in the price of food (wheat). The results show that the negative impacts of food price increase on school enrollment differ by gender, economic status, and the presence of siblings. The negative effects on school do not directly correspond to the increase in child labor because the transition from being idle to labor activity or from school to being idle are significant, particularly among the poor girls. The results also show that children in households with access to agricultural land are not affected by higher food prices. The analyses reveal a more dynamic picture of the impact of food price increase on child status and contribute to broader policy discussion to mitigate the impact of crises on children's education.